(untitled) (Research, Society and Development, 2020)
The genus Jatropha, is part of the Euphorbiaceae family. This family comprises 290 genera and approximately 7500 species, distributed throughout the world, mainly in tropical regions. This study aimed to prospect for patents on the main biological applications of the genus Jatropha. To carry out the research, the databases National Institute of Industrial Property of Brazil (INPI), European Patent Office (Espacenet), United States Patent and Trademark Office (USPTO), World Intellectual Property Organization (WIPO) and the descriptors A The WIPO database obtained the highest number of patents (n = 724), with the C12N classification predominating (n = 153). The number of patents filed on the Jatropha plant genus can be considered high when researched in general (n = 1434), however, when specifying only the pharmacological effects of the genus, few patent deposits are found (n = 38), which demonstrate the lack of incentive in the registration of patents for this technology in the pharmacological area, despite being a field of commercial interest, as well as a direction of scientific research in meeting the real needs of society and the economic sector.